Use of personal protective equipment in a radiology room at a veterinary teaching hospital - Mayer, Monique N.; Koehncke, Niels K.; Belotta, Alexandra F. [UNESP]; Cheveldae, Isaac T.; Waldner, Cheryl L. (Wiley-Blackwell, 2018)
The use of personal protective equipment by veterinary workers during radiographic imaging is inconsistent. While the self-reported use of leaded aprons and thyroid shields approaches 100% in some studies, the use of leaded gloves and eyeglasses is much lower. Previous studies describing personal protective equipment use are based on self-reporting. Objectives of this prospective, observational study were to describe use of leaded personal protective equipment during radiographic imaging by veterinary workers, and to compare observed use with self-reported use. Use of leaded personal protective equipment during radiographic imaging by veterinary workers was observed over a 10week period using two motion-triggered video cameras, and a questionnaire was then completed by workers on their use of personal protective equipment. Workers restrained the animal during 91.8% (753/820) of exposures. An apron and a securely closed thyroid shield were worn for>99% of studies. Gloves were used correctly for 43.6% (156/358) of radiographic studies. Leaded eyeglasses were worn for 1.7% (6/358) of studies. Correct glove use was more frequent during regular working hours than after-hours for both veterinarians (odds ratio 32.7, P=0.001) and veterinary students (odds ratio 75.1, P<0.001). The number of workers in the room was lower when animals were sedated (P=0.002) or anesthetized (P=0.017). Workers overestimated their frequency of glove use (P<0.001). In conclusion, workers use personal protective equipment less frequently in an unsupervised environment, and overestimate their use of personal protective equipment. Use of sedation or anesthesia decreases worker exposure to ionizing radiation.
Keywords: as low as reasonably achievable; occupational; safety